Distribution and Sources Of Polychlorinated Biphynal(PCB) in Sediment of The Coastal Area of Iraq: Distribusi dan Sumber Bifenil Poliklorinasi (PCB) dalam Sedimen di Wilayah Pesisir Irak - AL-Kayoon, Huda.Hassan; Huntosh, Ayad; AL-Saad, Hamid (Universitas Muhammadiyah Sidoarjo, 2024)
The concentrations of Σ13 PCBs compound in sediment samples were determined and analyzed at each site by using gas chromatography-mass spectrometry (GC–MS, Agilent), six stations were chosen along iraqi Coast, at Basrah city, south of Iraq. The Σ13 (PCB-18, PCB-29, PCB-31, PCB-28, PCB-44, PCB-52, PCB-101, PCB-141, PCB-149, PCB-138, PCB-153, PCB-189, and PCB-194)it recorded the highest concentration of PCB18 (0.351ng/g) in the sediment samples were found at station 3 and the lowest concentration was recorded in station 2 (0.150 ng/g),PCB 28 it found its highest concentration (0.299ng/g)in station 2 and lowest concentration (0.006 ng/g)were found at station five ,the highest concentration of PCB 29 (0.149 ng/g)in station1 and lowest concentration were found (0.007 ng/g) in station 3 ,as for PCB31 it had the highest concentration (0.106 ng/g) at station 1 and lowest concentration (0.014 ng/g) at station 2, PCB44 its highest concentration (0.138 ng/g) in 5 station while its lowest concentration (0.019 ng/g) in station 2. ,PCB52 highest concentration (0.492 ng/g) in station 5 while less concentation (0.068 ng/g) at station 4 ,highest concentration of PCB101(0.208 ng/g) in station 3 and lowest concentration (0.024 ng/g) at station 1 ,PCB138 highest concentration (0.042 ng/g) in station 4 and lowest concentration (0.010 ng/g) in station 2,PCB141 highest concentration (0.230 ng/g) at station 4 and lowest concentration (0.003 ng/g ) at station 3 ,PCB149 highest concentration (0.190 ng/g) a ant station 1and lowest concetration (0.022 ng/g) at ,the ]station 2. concentration PCB153 (0.210 ng/g) in station 3 was while it was less (0.016 ng/g) in station 2 ,it also had the highest concentration of PCB189 (0.166 ng/g ) in station 1 while the lowest concentration was found in the station 5 (0.010 ng/g) ,the highest concentration of PCB194 was measured at the station 2 and was (0.277 ng/g) and the lowest concentration at the station 3(0.017 ng/g). This project is the first of its kind in Basrah and first in the area . this study of PCB concentrations in the region could be used as a baseline study and can be used for subsequent studies.If we compare these data with other study in world it could be lies with other study in the world. The main sources of the PCB in sediment could be anthropogenic sources. Highlights: Study Overview: First PCB baseline study in Basrah, analyzing 13 compounds. Key Findings: PCB concentrations vary significantly across six coastal stations. Sources: PCB contamination primarily attributed to anthropogenic activities Keywords: PCBs, sediment , GC-MS.